Percepção dos consumidores de cosméticos eróticos sobre a efetividade, segurança e qualidade destes produtos - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
The search for erotic products that promote satisfaction in sexual life is present in our society and their purchase by the population has increased. Among the products sold are erotic cosmetics. Despite the availability of these products in sex shops, there are few studies that address issues related to their post-marketing surveillance. The objective of this work was to verify the perception of consumers of erotic cosmetics about the effectiveness, safety and quality of these products. A cross-sectional, descriptive and quali-quantitative research was carried out, where a questionnaire was applied to consumers who use or have used erotic cosmetics, over 18 years old and who agreed to participate in the research by signing the free and informed consent form. This questionnaire was made available online and in person to consumers who attended two sexshops in Macapá. 90 consumers participated in the survey. Most consumers are young women with higher education. The most commonly purchased cosmetics by sexshop consumers were gels (n=82). Physical sexshops were the most popular establishments for purchasing this type of product (n= 148). When the individual is going to choose a product to use, it is observed that the information given by the owner of the sex shop. The majority of respondents 88.9% (n=80) stated that the use of erotic cosmetics added benefits to their sex life, whether in their own personal satisfaction or that of their partner and reported not having had any adverse events related to the use of these products. Thus, consumers of erotic cosmetics have a good perception of the effectiveness, safety and quality of these products.
Keywords: Vigilância de Produtos Comercializados; Cosméticos eróticos; Cosmetovigilância; CNPQ::CIENCIAS DA SAUDE::FARMACIA; ODS 3 – Saúde e bem-estar